1993
DOI: 10.1021/jm00060a019
|View full text |Cite
|
Sign up to set email alerts
|

N-(1-Methyl-5-indolyl)-N'-(3-pyridyl)urea hydrochloride: the first selective 5-HT1C receptor antagonist

Abstract: The 5-HTic receptor was first characterized by Pazos1 in 1984. It is present in high levels in the choroid plexus epithelial cells with at least 10-fold lower densities in other brain regions of both rat2 and humans3•4 and is linked to the phosphatidyl inositol hydrolysis secondary messenger system5•6 as is the 5-HT2 receptor.5•7 In addition to sharing the same secondary messenger system, both the 5-HTic and 5-HT2 receptors have similar gene sequences with 79% homology in the seven transmembrane domains in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1

Year Published

1994
1994
2006
2006

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 4 publications
0
37
1
Order By: Relevance
“…Schild regression analysis yielded pA2 estimates of 7.2 for SB 200646 and 7.3 for mianserin (Figures 2 and 3). The slopes of the regression were 1.05 and receptors (pKi = 6.86; Forbes et al, 1993). The finding that yohimbine also possessed antagonist activity in rat jugular vein at concentrations consistent with its pA2 at 5-HT2B receptors permits further definition of the subtype involved.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Schild regression analysis yielded pA2 estimates of 7.2 for SB 200646 and 7.3 for mianserin (Figures 2 and 3). The slopes of the regression were 1.05 and receptors (pKi = 6.86; Forbes et al, 1993). The finding that yohimbine also possessed antagonist activity in rat jugular vein at concentrations consistent with its pA2 at 5-HT2B receptors permits further definition of the subtype involved.…”
Section: Resultsmentioning
confidence: 77%
“…We have recently demonstrated that a novel ligand, SB 200646 (N-1-methyl-5-indolyl)-N'-(3-pyridyl) urea HCI) exhibits moderate affinity for cloned rat 5-HT2c receptors and putative 5-HT2B receptors in rat stomach fundus, but little or no affinity for rat 5-HT2A and many other 5-HT receptors (Forbes et al, 1993;Baxter et al, 1994 (Bodelsson et al, 1992) for the 2nd agonist concentration-effect curve by that for the 1st concentration-effect curve constructed in the presence and absence of antagonist respectively. Tissues were equilibrated with antagonists for 1 h before the construction of second concentration-effect curves.…”
Section: Introduction Methodsmentioning
confidence: 99%
“…It seems, therefore, that additional properties of these antimigraine drugs, for example, the vasoconstriction in the extracerebral cephalic circulation with methysergide, ergotamine and dihydroergotamine (partly via 5-HT,-like receptors) and the antidepressant action with pizotifen, may be involved in their therapeutic action . Based mainly on the ability of a 5-HT,e receptor agonist, m-chloro-phenyl piperazine, to elicit migraine-like headaches in some patients and the ability of drugs such as mianserin to block this receptor, it has been advocated that 5-HTZc receptor antagonism is important for antimigraine action (Fozard and Gray, 1989;Fozard, 1992;Kennett, 1993). It should be noted, however, that m-chloro-phenyl-piperazine is not a selective agent and drugs that block the 5-HTzc receptor (e.g.…”
Section: Migrainementioning
confidence: 99%
“…The initial use of nonselective antagonists for 5-HT 2B/2C receptors (3,4), followed by analysis of the behavioral effects of SB R.N. Takahashi et al 200646A, a selective, albeit weak, antagonist of these receptors (5), has indicated that blockade of 5-HT 2B/2C receptors may actually be endowed with anxiolytic properties (6). Such an intrinsic property of 5-HT 2B/2C receptor antagonists has raised interest with regard to the therapy of anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%